1982
DOI: 10.1128/iai.36.2.696-703.1982
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of innate susceptibility to Salmonella infection and endotoxin responsiveness in C3HeB/FeJ mice and other strains in the C3H lineage

Abstract: Studies of various mouse strains in the C3H lineage have shown that there is no correlation between innate susceptibility to Salmonella infection and sensitivity to the toxic or mitogenic effects of lipopolysaccharide (LPS). C3H/HeNCrlBR mice were Salmonella resistant, but sensitive to the toxic and mitogenic effects of LPS, whereas C3HeB/FeJ mice were Salmonella susceptible as the C3H/HeJ mice, yet were mitogenically responsive to LPS and sensitive to its lethal effects. Furthermore, other mouse strains (C3H/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Research using mouse typhoid infections has supported this view. Different C3H lineage mice, either unresponsive or highly susceptible to the toxic effects of injected LPS, died with equivalent lethal loads of salmonellae (Eisenstein et al, 1982), arguing against a role for endotoxin in causing death in salmonellosis. This view was also endorsed by Collins (1979).…”
Section: Discussionmentioning
confidence: 99%
“…Research using mouse typhoid infections has supported this view. Different C3H lineage mice, either unresponsive or highly susceptible to the toxic effects of injected LPS, died with equivalent lethal loads of salmonellae (Eisenstein et al, 1982), arguing against a role for endotoxin in causing death in salmonellosis. This view was also endorsed by Collins (1979).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the M ¤ inflammatory response is crucial to control S. typhimurium infections, since the M ¤ -depleted mice were not able to control the infection. Indeed, it has been shown that mice which have a genetic defect in the lps gene and which are therefore hyporesponsive to the biological effects of LPS, are not able to control S. typhimurium infections [31]. Certainly, additional experiments involving the measurement of inflammatory cytokines during S. typhimurium infection in M ¤ -depleted mice are warranted to provide more insight into how the M ¤ -Salmonella interaction initiates pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The innate susceptibility or resistance of mice to S. typhimurium infection is governed by several genes (13,27,(45)(46)(47), and differences in the genetic background between nonresponder and responder mouse strains may contribute to this heterogeneity through the growth and/or elimination rate of S. typhimurium. For instance, we showed that following i.p.…”
Section: Discussionmentioning
confidence: 99%